1978
DOI: 10.1159/000152933
|View full text |Cite
|
Sign up to set email alerts
|

The Nubians of Kom Ombo: Serum and Red Cell Protein Types

Abstract: Phenotype and gene frequencies are presented for eight polymorphic systems among the Nubians of South Egypt, namely, acid phosphatase, glucose-6-phosphate dehydrogenase, adenylate kinase, 6-phosphogluconate dehydrogenase, esterase D, phosphoglucomutase I, peptidase A, and haptoglobin. Eleven systems, namely, albumin, ceruloplasmin, hemoglobin, lactate dehydrogenase, isocitrate dehydrogenase, phosphohexose isomerase, malate dehydrogenase, peptidase B and C, phosphoglucomutase II, and transferrin were found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
5
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
6
5
0
Order By: Relevance
“…The frequency of G6PD deficiency we report here for Egyptians, Irianians, and Lebanese are in general agreement with previous reports [13, 14, 15, 16](table 4). However, we obtained a frequency of 3.6% for Jordanians.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The frequency of G6PD deficiency we report here for Egyptians, Irianians, and Lebanese are in general agreement with previous reports [13, 14, 15, 16](table 4). However, we obtained a frequency of 3.6% for Jordanians.…”
Section: Discussionsupporting
confidence: 93%
“…This frequency is, however, lower than the previously reported values of 0–2% for Egypt [13, 14], 1.7% for Jordan [17], and 3.09% for Lebanon [23]. An earlier study carried out in Kuwait in 1966 in 118 samples, using the field screening method (the methaemoglobin reduction test), reported a deficiency rate of 18.9% for the entire population [24].…”
Section: Discussionmentioning
confidence: 64%
“…The same slow variant of ceruloplasmin has been detected among the Fur and Baggara tribes of Jabal Marra area of the Sudan (Bayoumi et al, 1985). However, no variant form of the protein has been detected in a random sample from Khartoum (Saha et al, 1978); tribes of western Saudi Arabia @aha et al, 1979), or Egyptian Nubians (Bertin et al, 1978).…”
Section: Serum Proteinsmentioning
confidence: 78%
“…(Bayoumi et al, 1979;Banerjee et al, 1981, Saha and Banerjee, 1986, Hamza et al, 1976, although isolates of Shiati Arabs from eastern Saudi Arabia have a high Hbs frequency (Lehmann et al, 1963, Goedde et al, 1979. The Nubians of southern Egypt and northern Sudan also do not seem to possess HbS (Awny et al, 1965;Azim et al, 1974;Bertin et al, 1978). On the other hand, the introduction of Hbo-Arab is probably due t o Arab elements from North Africa .…”
mentioning
confidence: 99%
“…The variants could be identified as PHI 2-1, 3-1, and 4-1 according to Giblett (1969). No such variants of PHI were found among the Fur and other Sudanese tribes previously studied, but Bertin et al (1978) reported a single PHI variant among the Nubians of Kom Ombo in Egypt. It was not possible to establish the genetic nature of these variants because family sizes were not sufficient.…”
mentioning
confidence: 69%